Efectos del diseño del tutor para el mantenimiento y soporte de la planta de la pitahaya (Hylicereus megalanthus) en el Ecuador” - Vera Guerrero, José Steven (2022)
This document deals with the stakes that can be adapted to the cultivation of pitahaya (Hylocereus megalanthus). This fruit is considered highly demanded abroad due to its nutritional properties; therefore, the production of this cactus must be optimal to achieve the necessary quality standards that position this fruit suitable for export. The design of a good stake guarantees a good phenological development of the crop to obtain quality fruit. A good tutor could help improve field work which can reduce maintenance costs. The conclusions determine that the use of living tutors leads to more work in the field due to the maintenance that these need due to the need for pruning every certain period, which may help to develop the different field tasks such as fertilization, pest control, pruning and harvesting of the cactus.